Youth unemployment after apprenticeship training and individual, occupation and training employer characteristics - Mohrenweiser, Jens [Verfasser]; Zwick, Thomas [Verfasser] (My University, 2015)
"This paper analyses the risk of unemployment, unemployment duration and the risk of longterm unemployment immediately after apprenticeship graduation. Unemployed apprenticeship graduates constitute a large share of unemployed youth in Germany but unemployment incidence within this group is unequally distributed. Our paper extends previous research in three dimensions. It shows that individual productivity assessment of the trainig firm, initial selection into high reputation trainig firms and occupations, and adverse selection of employer moving graduates are correlated with unemployment after apprenticeship graduation." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.2.2.4 Arbeitslosigkeit; Ausbildungsabsolvent; Arbeitsmarktrisiko; Jugendarbeitslosigkeit; Einflussfaktor; Ausbildungsbetrieb; Persönlichkeitsmerkmal; Personalauswahl; Linked-Employer-Employee-Panel